Consumption in Action. Mapping Consumerism in International Academic Literature - Pattaro, Chiara; Setiffi, Francesca (PARTECIPAZIONE E CONFLITTO, 2017)
The consumer-citizen and more generally, the emergence of active forms of citizenship mediated by consumption point to a change in the relations of production, consumption and distribution. These forms of citizenship come to encompass opposite poles of consumption such as hedonism and social responsibility. When consumption choices are associated with the social and environmental issues connected to manufacturing and distribution processes, the space claimed by the active consumer comes to represents a form of social identity recognition. This ‘political’ sphere, made up of individual and/or collective claims mediated by consumer society comes in the wake of a long period of market de-politicization. On the basis of these assumptions, this article surveys and evaluates the topics related to critical consumption that are most discussed in the social sciences. Such forms of socially oriented consumption – enacted in the form of individual or collective consumer choices – represent a new form of political participation and are understood as practices of active-citizenship promotion. The findings of this article are based on data gathered from 478 peer-reviewed articles published between 2004 and 2013. The articles were selected from Scopus on the basis of their broad connection to critical consumerism and forms of socially oriented consumerism. A software-based content analysis run through T-Lab software was used to generate an analytical model of the main research axis of the most recent international literature on these arguments. The heterogeneous body of scholarly literature on socially oriented consumption reflects the rich diversity of perspectives adopted to understand the political and ethical role of consumers in contemporary societies